2016
DOI: 10.1177/016146811611800504
|View full text |Cite
|
Sign up to set email alerts
|

Educational Expectations and Progress of Community College Students: Does Socialization Matter?

Abstract: Background While literature is abundant on factors associated with community college student outcomes, limited attention has been paid to what shapes educational expectations after students enroll, and how these expectations are linked to educational progress. To address this gap, Weidman's (1989) undergraduate socialization theory is particularly relevant, as this theory not only applies to traditional-age college students, but also to adults of varying ages who constantly adapt themselves to changing circums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…More relevantly, Renzulli and Barr [ 36 ] reported that both the degree and institutional route expectations of grade-9 adolescent students significantly predicted their degree expectation in grade 11 while accounting for family SES and family economic shocks, in which the degree and institutional route expectations of adolescent students were less adversely affected by family SES and family economic shocks in the lower socioeconomic-status group compared to their counterparts in middle-class status. As educational expectations of youths have been empirically reported as valuable individual resources promotive of youths’ educational development [ 37 , 38 ], we anticipate in this study that educational expectations of youths would promote youths’ academic commitment and educational performance in middle school and educational achievement in adulthood, in which youths’ academic commitment and educational performance would mediate the effect of youths’ educational expectations on their educational achievement in adulthood.…”
Section: Introductionmentioning
confidence: 98%
“…More relevantly, Renzulli and Barr [ 36 ] reported that both the degree and institutional route expectations of grade-9 adolescent students significantly predicted their degree expectation in grade 11 while accounting for family SES and family economic shocks, in which the degree and institutional route expectations of adolescent students were less adversely affected by family SES and family economic shocks in the lower socioeconomic-status group compared to their counterparts in middle-class status. As educational expectations of youths have been empirically reported as valuable individual resources promotive of youths’ educational development [ 37 , 38 ], we anticipate in this study that educational expectations of youths would promote youths’ academic commitment and educational performance in middle school and educational achievement in adulthood, in which youths’ academic commitment and educational performance would mediate the effect of youths’ educational expectations on their educational achievement in adulthood.…”
Section: Introductionmentioning
confidence: 98%
“…Some universities may not accept certain courses or credits earned at community colleges, leading to the need for students to retake courses, which can be time-consuming and costly. Students from community colleges may also face challenges in adapting to the different academic expectations, teaching methods, and campus cultures at universities (Wang, 2016). They may need additional support and resources to succeed in the new environment.…”
Section: Challenges In Integrating University and Community College T...mentioning
confidence: 99%